Relationship between Knowledge and Compliance Using Anti-dyslipidemic Drugs among Hypertensive Patients with Dyslipidemia in Bandung, West Java, Indonesia - Sitti Alifa Batasalsabilla; Kuswinarti Kuswinarti; Rudolf Andean (Althea Medical Journal)
Background: Dyslipidemia occurs in 60% of hypertensive patients. Effective treatment of hypertensive patients with dyslipidemia can reduce the risk of cardiovascular disease by more than 50%. However, compliance with dyslipidemia medication in dyslipidemia patients is still low. Low compliance can be attributed to poor knowledge. This study aimed to analyze the relationship between knowledge and compliance using antidyslipidemic drugs in hypertensive patients with dyslipidemia.